Economic-Social-Environmental Measurements as Indicators of the Sustainability of the Kintamani Tourist Destination - I Ketut Putra Suarthana; Ni Luh Putu Agustini Karta; Ni Made Ary Widiastini; Erna Zulaini Wiles (Bali Journal of Hospitality, Tourism and Culture Research, 2026)
This study examines the sustainability and governance of tourism destinations in the Mount Batur Kintamani. A qualitative approach was employed through in-depth interviews with 33 informants representing eleven stakeholder groups, including government, local communities, MSMEs, tourism actors, and academics, supported by secondary statistical data. Data were analyzed using thematic coding, with sustainability indicators operationalized through stakeholder perceptions of economic benefits, social capacity, governance practices, and environmental pressures. The findings show that post-eruption tourism contributes positively to local livelihoods through income diversification across MSMEs, agriculture, fisheries, hospitality, and tour services. However, these benefits are unevenly distributed and accompanied by governance challenges, such as limited stakeholder coordination, environmental pressures from mining and high visitor intensity, and social capacity gaps. Environmental risks and disaster vulnerability further complicate sustainability outcomes, revealing trade-offs between economic dependence on tourism and long-term ecological resilience. From a governance perspective, sustainability in volcanic geo-tourism is shaped primarily by stakeholder coordination and governance capacity rather than hazard intensity alone. The study contributes theoretically interpretative governance lens for analyzing sustainability trade-offs in disaster-prone tourism contexts. Managerially, it highlights the need for inclusive, coordinated, and risk-sensitive governance to support long-term geo-tourism sustainability.